Empowering Language Learning: Harnessing Padlet to Assist Non-English Department Students in English Learning - Sahyoni Sahyoni; Lena Sastri (SALEE: Study of Applied Linguistics and English Education, 2023)
In this digital era, the emergence of technology for language instruction is unquestionable. Technology helps students learn a target language more quickly, easily, and happily than traditional methods. The non-English department requires extra inspiration, motivation, and a unique approach. As an ICT platform, Padlet is regarded as a creative medium for English learning. This study provides light on how the padlet application can be used to assist and motivate non-English Department students to learn English. This study utilized a quantitative methodology with a sample of 38 people. These participants were all first-year non-English Department Mandailing Natal, STAIN Mandailing Natal Sumatera Utara. The PIAUD (early childhood Islamic education) department had 19 participants, while the Perbankan Syariah (Islamic banking) department had 19 students. For data collection, the researcher utilized a questionnaire. The questionnaires collect baseline information regarding the use of padlet as an innovative medium for English learning. This study found that the majority of students (80%) believe padlet to be a suitable and dynamic medium for learning English, and students are motivated to study English. Keywords: Non-English department, learning English, padlet.